2011
DOI: 10.1364/oe.19.003647
|View full text |Cite
|
Sign up to set email alerts
|

05 µJ pulses from a giant-chirp ytterbium fiber oscillator

Abstract: We present a mode-locked all-normal dispersion ytterbium fiber oscillator with output pulse energies beyond 0.5 µJ. The oscillator is mode-locked using nonlinear polarization rotation, and stable single-pulse operation is achieved by spectral filtering inside the resonator. The oscillator generates strongly chirped output pulses at a repetition rate of 4.3 MHz which can be compressed down to 760 fs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Usually, dissipative soliton pulses from all-normal dispersion (ANDi) lasers are compressible almost to the transform-limited value [83,84]. Nevertheless, the performance of the graphene-based YDFLs is far worse than of YDFLs utilizing other mode-locking techniques, such as NOLM/NALM, SESAM, or NPR, where broadband spectra with large pulse energies are achieved [85][86][87].…”
Section: Ytterbium-doped Fiber Lasersmentioning
confidence: 99%
“…Usually, dissipative soliton pulses from all-normal dispersion (ANDi) lasers are compressible almost to the transform-limited value [83,84]. Nevertheless, the performance of the graphene-based YDFLs is far worse than of YDFLs utilizing other mode-locking techniques, such as NOLM/NALM, SESAM, or NPR, where broadband spectra with large pulse energies are achieved [85][86][87].…”
Section: Ytterbium-doped Fiber Lasersmentioning
confidence: 99%
“…Ultrafast Yb-doped fiber laser sources have been rapid development over the past decade due to their numerous applications, and they have become popular in the research fields [1][2][3], especially in 980 nm wave band. 980 nm fiber laser has a significant application which is important for generation the blue-green sources through frequency-doubled to 488-490 nm light, and has been also widely reported pumping Er-doped fiber amplifiers/lasers thanks to their excellent beam quality, small volume and simpler thermal management [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] In 2008, Chong et al identified the influence of the total cavity dispersion on the output characteristics of ANDi fiber lasers, and showed that to minimize the pulse duration the cavity dispersion should be as small as possible, and for a fixed cavity dispersion increasing pulse energy leads to shorter pulses with more structured spectra. [25] In conjunction with this idea, it has been shown that, by increasing the total cavity dispersion with lengthening the passive fiber section, giant dissipative solitons with narrow spectrum and large pulse energy may be generated, [26][27][28] or, by decreasing the total cavity dispersion very short femtosecond pulses may be achieved with the ANDi fiber laser. [29,30] In 2009, Sayinc demonstrated that the compressed pulse under 100 fs may also be achieved for the ANDi fiber laser with large total cavity dispersion.…”
Section: Introductionmentioning
confidence: 99%